The efficacy and safety of neoadjuvant immunotherapy in resectable locally advanced esophageal squamous cell carcinoma: A systematic review and meta-analysis - He, Wenwu; Wang, Chenghao; Li, Changding; Nie, Xin; Li, Haojun; Li, Jialong; Zhao, Na; Chen, Haijun; Miao, Xiaojie; Han, Yongtao; Peng, Lin; Leng, Xuefeng (Frontiers in Immunology, 2023)
Objective: This systematic review and meta-analysis aimed to explore the efficacy and safety of neoadjuvant immunotherapy in patients with resectable locally advanced esophageal squamous cell carcinoma (ESCC). Background: Several studies have reported the outcomes of neoadjuvant immunotherapy in patients with ESCC. However, phase 3 randomized controlled trials (RCTs) with long-term outcomes and the comparison of different therapeutic strategies are lacking. Methods: Studies involving patients with advanced ESCC treated with preoperative neoadjuvant immune checkpoint inhibitors (ICIs) were searched through PubMed, Embase, and Cochrane Library up to July 1, 2022. The outcomes were presented as proportions and pooled respectively by fixed or random effect model depending on the heterogeneity between studies. All analyses were performed using the R packages meta 5.5-0 and meta-for 3.4-0. Results: Thirty trials involving 1406 patients were included in the meta-analysis. The pooled pathological complete response (pCR) rate for neoadjuvant immunotherapy was 0.30 (95% confidence interval [CI]: 0.26–0.33). The pCR rate of neoadjuvant immunotherapy combined with chemoradiotherapy (nICRT) was significantly higher than that of neoadjuvant immunotherapy combined with chemotherapy (nICT) (nICRT: 0.48, 95% CI: 0.31–0.65; nICT: 0.29, 95% CI: 0.26–0.33; p=0.03). No significant difference in efficacy was observed between the different chemotherapy agents and treatment cycles. The incidences of grade 1–2 and 3–4 treatment-related adverse events (TRAEs) were 0.71 (95% CI: 0.56–0.84) and 0.16 (95% CI: 0.09–0.25), respectively. Patients treated with nICRT and carboplatin had a higher incidence of grade 3–4 TRAEs compared with those treated with nICT (nICRT: 0.46, 95% CI: 0.17–0.77; nICT: 0.14, 95% CI: 0.07–0.22; p=0.03) and cisplatin (carboplatin: 0.33, 95% CI: 0.15–0.53; cisplatin: 0.04, 95% CI: 0.01–0.09; p<0.01). Conclusion: Neoadjuvant immunotherapy has good efficacy and safety profiles in patients with locally advanced ESCC. Additional RCTs with long-term survival data are warranted.